Composite resin restoration with fiber reinforced composite after root canal treatment of necrotic pulp tooth with gumboil - Dessy Natalia; Yulita Kristanti (Universitas Gadjah Mada, 2021)
Gumboil is inflammation reaction in the gum caused by pulp infection. Gumboil is seen as an oral lesion characterized by a soft erythematous papule where a periapical abcess is draining into the oral cavity. An adequate root canal treatment can cure gumboil and remove bacteria from the root canal. To support the success of root canal treatment, final restoration used in this case is composite resin restoration with reinforcing fiber (short fiber reinforced composite). The purpose of this treatment was to restore the functions of tooth in mastication and preserving the supporting tissue. A female patient age 23 years old came with complaints of pain in the lower right mandibular molar accompanied by swelling of the gums around the teeth since a week ago. Swelling is intermittent since last 3 months. The tooth have been restored for about 3 years ago. Clinical examination showed a positive percussion, positive palpation, negative vitality, and negative mobility. Radiographic examination showed bifurcation and periapical lesions. Root canal treatment is performed with crown down preparation technique and followed by direct composite resin restoration with short fiber reiforced composite. The success of root canal treatment followed by composite resin restoration with short fiber reinforced fiber is marked by the absence of complaints as well as the dissappearance of gumboil.